2018
DOI: 10.3390/s18072063
|View full text |Cite
|
Sign up to set email alerts
|

FluoSpec 2—An Automated Field Spectroscopy System to Monitor Canopy Solar-Induced Fluorescence

Abstract: Accurate estimation of terrestrial photosynthesis has broad scientific and societal impacts. Measurements of photosynthesis can be used to assess plant health, quantify crop yield, and determine the largest CO2 flux in the carbon cycle. Long-term and continuous monitoring of vegetation optical properties can provide valuable information about plant physiology. Recent developments of the remote sensing of solar-induced chlorophyll fluorescence (SIF) and vegetation spectroscopy have shown promising results in us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 64 publications
2
51
0
Order By: Relevance
“…The relative importance analysis conducted in this study confirmed that PAR in is one of the primary drivers to the strong positive GPP:SIF relationship and supported our hypothesis that the drivers vary at different temporal scales. At a time scale with small variations in canopy structure (indicated by fPAR) and physiology (indicated by LUE and F 760,y ), for example, the VT and R1–R3 stages of the maize fields in this study, PAR in has a dominant influence on the GPP:F 760 relationship, which has been well acknowledged in the SIF community (Goulas et al, ; Miao et al, ; K. Yang, Ryu, et al, ; X. Yang, Shi, et al, ). The LUE:F 760,y relationship exhibited either a negative pattern or no clear pattern (Figure and Table ), which explained some of the deviations from a strong linear pattern in the GPP:F 760 relationship.…”
Section: Discussionmentioning
confidence: 53%
See 4 more Smart Citations
“…The relative importance analysis conducted in this study confirmed that PAR in is one of the primary drivers to the strong positive GPP:SIF relationship and supported our hypothesis that the drivers vary at different temporal scales. At a time scale with small variations in canopy structure (indicated by fPAR) and physiology (indicated by LUE and F 760,y ), for example, the VT and R1–R3 stages of the maize fields in this study, PAR in has a dominant influence on the GPP:F 760 relationship, which has been well acknowledged in the SIF community (Goulas et al, ; Miao et al, ; K. Yang, Ryu, et al, ; X. Yang, Shi, et al, ). The LUE:F 760,y relationship exhibited either a negative pattern or no clear pattern (Figure and Table ), which explained some of the deviations from a strong linear pattern in the GPP:F 760 relationship.…”
Section: Discussionmentioning
confidence: 53%
“…The GPP:SIF relationship was reported to be consistently positive in previous studies, and our current study at the two maize sites confirmed the positive pattern. The LUE:SIF y relationship was different from the GPP:SIF relationship and exhibited various patterns from different studies (Damm et al, ; Miao et al, ; Wieneke et al, ; K. Yang, Ryu, et al, ; X. Yang, Shi, et al, ; Yang et al, ). Although the mechanism of the various LUE:SIF y relationship is still in debate, our current study indicated that the LUE:SIF y relationship varied at different temporal scales and at different growth crop stages.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations